The 1913 and 1914 white workers' strikes - O'Quigley, A. (My University, 1978)
The gold mining industry on the Rand began in the 1880's and by 1913 there were 63 mines employing about 21 000 white workers and 200 000 black workers. Gold, the international money commodity, had a fixed price. This meant there was a certain constraint with regard to the costs of production because increases could not be passed on to the buyers. The gold bearing ore on the Rand was deep lying and of a consistent low grade throughout the Reef. Because of its depth large amounts of capital investment were required for its exploitation. This was provided by finance houses in Europe through whom groups of gold mining companies were controlled. The profitability of the industry was constrained by the fixed price, the low grade of the ore and the need for large scale capital investment. Because of this the industry depended on cheap labour. The problem of finding and maintaining a supply of cheap labour dominated the policies of the industry. In the early years the great majority of blacks lived in the rural areas subsisting as independent farmers or on white owned land as squatters, share croppers and wage labourers…. As far as the gold mining industry was concerned in the early years some blacks came voluntarily in order to obtain cash to buy European produced goods such as guns. But increasingly black labour was obtained by recruiters who worked for the gold mining industry…. The black labour force thus obtained was lacking in any experience of industrial life and was restricted to unskilled work. In order to develop the mines and carry out certain skilled mining operations the gold companies also needed a supply of skilled workers. These were not available in South Africa. Skilled miners from overseas were induced £o come to the. Witwatersrand because of the relatively high wages. Most of them originated in Britain. Skilled miners tended to be nomadic and some had experience of work in Australia, America and other gold fields throughout the world. These miners' brought to South Africa their trade union experience and soon established branches of British craft unions and an autonomous miners union. As blacks became experienced in gold mining operations the TCM wanted to be able to substitute this labour for the more expensive white workers. Skilled whites were still necessary but where skills could be fragmented blacks could carry out some of the operations…. This is largely an empirical study of the 1913 miners' strike and the 1914 railway strike. I concentrate on events rather than analysis and would be glad of any help from people in the seminar. Although it is impossible to exhaustively state the causes for the 1913 strike I outline some of the factors I see as important. These include the insecurity of white miners because of their fear of being replaced by black and their reaction to general labour condition including their insecurity of tenure and the occupational disease phthisis. The strike itself revolved around the question of the recognition of trade unions which the TCM refused to do.
African Studies Seminar series. Paper presented October 1978
Keywords: Strikes and lockouts. Gold mining. South Africa; Strikes and lockouts. Miners. South Africa; Strikes and lockouts. Railroads. South Africa; Labor unions. South Africa